Vector-borne and zoonotic infections and their relationships with regional and socioeconomic statuses: An ID-IRI survey in 24 countries of Europe, Africa and Asia - Saydam, Fatma Nurhayat; Erdem, Hakan; Ankarali, Handan; El-Arab Ramadan, Manar Ezz; El-Sayed, Nagwa Mostafa; Civljak, Rok; Pshenichnaya, Natalia; Moroti, Ruxandra Valentina; Mahmuodabad, Fatemeh Moradi; Maduka, Agah Victor; Mahboob, Amjad; Prakash Kumari, Pilli Hema; et al. (Travel medicine and infectious disease, 2021)
BACKGROUND: In this cross-sectional, international study, we aimed to analyze vector-borne and zoonotic infections (VBZI), which are significant global threats. METHOD: VBZIs' data between May 20-28, 2018 was collected. The 24 Participatingcountries were classified as lower-middle, upper-middle, and high-income. RESULTS: 382 patients were included. 175(45.8%) were hospitalized, most commonly in Croatia, Egypt, and Romania(P = 0.001). There was a significant difference between distributions of VBZIs according to geographical regions(P < 0.001). Amebiasis, Ancylostomiasis, Blastocystosis, Cryptosporidiosis, Giardiasis, Toxoplasmosis were significantly more common in the Middle-East while Bartonellosis, Borreliosis, Cat Scratch Disease, Hantavirus syndrome, Rickettsiosis, Campylobacteriosis, Salmonellosis in Central/East/South-East Europe; Brucellosis and Echinococcosis in Central/West Asia; Campylobacteriosis, Chikungunya, Tick-borne encephalitis, Visceral Leishmaniasis, Salmonellosis, Toxoplasmosis in the North-Mediterranean; CCHF, Cutaneous Leishmaniasis, Dengue, Malaria, Taeniasis, Salmonellosis in Indian Subcontinent; Lassa Fever in West Africa. There were significant regional differences for viral hemorrhagic fevers(P < 0.001) and tick-borne infections(P < 0.001), and according to economic status for VBZIs(P < 0.001). The prevalences of VBZIs were significantly higher in lower-middle income countries(P = 0.001). The most similar regions were the Indian Subcontinent and the Middle-East, the Indian Subcontinent and the North-Mediterranean, and the Middle-East and North-Mediterranean regions. CONCLUSIONS: Regional and socioeconomic heterogeneity still exists for VBZIs. Control and eradication of VBZIs require evidence-based surveillance data, and multidisciplinary efforts.
Keywords: Animals; Zoonosis; Zoonoses; Europe; Asia; zoonózy; Vector; průřezové studie; Afrika; lidé; Evropa; Tick; Hemorrhagic Fever, Crimean; Hemorrhagic Fever Virus, Crimean-Congo; Cross-Sectional Studies; Africa; Socioeconomic Factors; hemoragická horečka krymská; Asie; virus krymsko-konžské hemoragické horečky; Economic status; socioekonomické faktory; zvířata; Infection; Humans